Health Belief Model Application on Food Safety Behavior of Bantul Beach Tourism Culinary Food Handlers - Asep Rustiawan; Ichtiarini Nurullita Santri; Yohane Abero Phiri (Universitas Ahmad Dahlan, 2023)
Background: Maintaining food safety is very important to reduce the incidence of foodborne diseases. Previous studies have shown that food safety is related to the healthy behavior of food handlers, while healthy behavior is related to their beliefs and perceptions. The Health Belief Model (HBM) is a theory with a concept of individual reasons for carrying out healthy behaviors based on the perception of disease threats and efforts to improve behavior when facing threats. This study aims to predict and analyze the effect of variables based on the HBM construct on food safety behavior. Method: A total of 80 food handlers from all seafood stalls on the Bantul coast were interviewed face to face using a printed questionnaire regarding seriousness, vulnerability, benefits, barriers, a stimulus to action, and self-efficacy. The food safety behavior of food handlers was observed using observation sheets. Data were evaluated using Structural Equation Model-Partial Least Square (SEM-PLS) Version 3.0. Results: HBM can predict 35.1% of food handlers' food safety behavior variance in the Bantul beach tourism culinary area (R2 adjusted = 0.351). Of all the HBM construct variables analyzed, two variables had a significant effect, namely the stimulus-to-act variable with a path coefficient value (Î² = 0.305, p = 0.009 <0.05) and the seriousness variable (Î² = 0.302, p = 0.045 <0.05). Conclusion: HBM succeeded in predicting the food safety behavior of food handlers in tourist culinary delights in Bantul, Yogyakarta, Indonesia. The stimulus-to-action variable was the strongest predictor positively affecting food handlers' food safety behavior, followed by the seriousness variable.